Implementasi Kebijakan Keamanan Lalu Lintas Dan Angkutan Jalan Di Kota Tangerang - Noviyanti, Evita; Sjafari, Agus; Listyaningsih (CV. Multi Kreasi Media, 2025)
This study aims to analyze the implementation of traffic and road transportation policy in Tangerang City using Edward III’s policy implementation theory, which includes four key dimensions: communication, resources, disposition, and bureaucratic structure. A qualitative approach was employed, with data collected through in-depth interviews with officials from the Department of Transportation, Police, Civil Service Police Unit (Satpol PP), as well as members of the public and road users such as online drivers. The findings reveal that communication among implementing agencies and with the public remains suboptimal due to inconsistent information and a lack of integrated communication channels. Limited human resources and budget constraints also hinder effective implementation, although efforts in training and digitalization have been initiated. The disposition of policy implementers is generally positive; however, the lack of adequate incentive systems reduces motivation and loyalty among both implementers and the public. Furthermore, the fragmented bureaucratic structure leads to overlapping duties and miscommunication between agencies, despite ongoing coordination through special teams and regular meetings. Based on these findings, strengthening public communication systems, enhancing the quality and quantity of resources, reforming performance-based incentives, and reorganizing a more integrated bureaucratic structure are necessary to ensure the success of traffic and transportation policy implementation in Tangerang City.